Myasthenia gravis and COVID‐19: A case series and comparison with literature. (29th April 2021) - Saied, Zakaria; Rachdi, Amine; Thamlaoui, Saber; Nabli, Fatma; Jeridi, Cyrine; Baffoun, Nader; Kaddour, Chokri; Belal, Samir; Ben Sassi, Samia
Abstract : Objective: To describe presenting symptoms, clinical outcomes, and therapeutic management of concurrent Coronavirus disease 2019 (COVID‐19) infections in patients with a pre‐existing myasthenia gravis (MG). Methods: We conducted a retrospective study in patients with preexisting MG presenting with concurrent COVID‐19 between September 21st and November 4th, 2020 when attending the emergency department or routine neurology consultation at the National Institute Mongi Ben Hamida of Neurology of Tunis, Tunisia. Results: Five patients were identified. The Myasthenia Gravis Foundation of America scores (MGFA) prior to COVID‐19 infection were class I in one patient, class II (IIa, IIb) in two patients, and class IIIb in one patient. Four patients had mild to moderate courses of COVID‐19 infection. One patient presented a critical infection with acute respiratory disease syndrome (ARDS) requiring mechanical ventilation. Two of them also demonstrated signs of MG exacerbation requiring the use of intravenous immunoglobulin in one case. We maintained immunosuppressant therapy to MG in all our patients. All our patients received Azithromycin (AZM) as a part of specific drug treatment of COVID‐19 infection. Outcome was favorable in 4 patients and rapidly fatal evolution was observed in the patient with ADRS. Discussions and conclusion: The results from our study suggest that prior MG activity could partially influence the subsequent clinical outcomes. It emerged also that ongoing long‐term immunosuppressive immunotherapy to MG should be maintained during the COVID‐19 pandemic and that AZM can be used safely in MG patients and concurrent COVID‐19 infection.